Cell-free therapy for canine osteoarthritis: current evidence and prospects. Issue 1 (31st December 2022) - Sharun, Khan; Muthu, Sathish; Mankuzhy, Pratheesh D.; Pawde, Abhijit M.; Chandra, Vikash; Lorenzo, Jose M.; Dhama, Kuldeep; Amarpal; Sharma, G. Taru
Abstract: Osteoarthritis is a progressive degenerative disease affecting joints. It is associated with structural and functional changes that cause lameness and pain in dogs. Mesenchymal stem cells (MSCs) are considered an ideal therapeutic candidate for treating inflammatory musculoskeletal conditions due to their paracrine and immunomodulatory characteristics. They are delivered intravenously or as intra-articular injections for treating canine osteoarthritis. However, ex vivo studies have confirmed that the osteoarthritic synovial fluid is cytotoxic to cultured MSCs. Therefore, intra-articular transplantation of viable MSCs should be considered counterproductive since it minimizes cellular viability. Similarly, the intravenous administration of MSCs limits the therapeutic effects on the organ of interest since most of the administered cells get trapped in the lungs. Therefore, cell-free therapeutic strategies such as conditioned media and extracellular vesicles (EVs) can potentially become the future of MSC-based therapy in managing canine osteoarthritis. It overcomes the limitations of MSC-based therapy, such as tumor differentiation, immunogenicity, and pulmonary embolization, and has advantages like low immunogenicity and off-shelf availability. In addition, they eliminate problems such as low cell survival, transmission of infections, and unpredictable behavior of the transplanted MSCs, thereby acting as a safe alternative to cell-based therapeutics. However, very limited data is available on the efficacy and safety of cell-free therapy using MSCs for managing canine osteoarthritis. Therefore, large-scale, multicentric, randomized clinical controlled trials are required to establish the therapeutic efficacy and safety of MSC-based cell-free therapy in clinical cases of canine osteoarthritis.